A new song [compact disc, unabridged] - Karon, Jan, 1937- (Karon, Jan, 1937- Mitford years., 1999)
Recently retired, Mitford's longtime Episcopal priest, Father Tim, fills in at a small church on Whitecap Island. He and his wife, Cynthia, soon find that Whitecap has its own unforgettable characters.